2021
DOI: 10.1007/s00431-021-04031-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transient congenital primary hypothyroidism: data from the German registry for congenital hypothyroidism (AQUAPE “HypoDok”)

Abstract: Neonatal screening for congenital primary hypothyroidism (CH) may not distinguish between transient (TCH) and permanent dysfunction (PCH), causing potential overtreatment and concerns in affected families. To specify the indication for interruption of therapy, we analysed the German registry “HypoDok” for infants with CH, which oversees 1625 patients from 49 participating centres in Germany and Austria from 1997 until today. A total of 357 patients with a thyroid gland in loco typico were identified and retros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
3
16
0
Order By: Relevance
“…The important question is if the screening TSH test can be useful to select the patients who could be treated less extensively to avoid overtreatment and reduce parents’ anxiety and medical care costs ( 30 32 ). It is known from other data that screening TSH tends to be lower in neonates with TCH than in those with PCH ( 17 , 33 35 ). In our study, decreased screening TSH results were observed in newborns with birth weight below -2 SDS who are mostly burdened with TCH risk.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The important question is if the screening TSH test can be useful to select the patients who could be treated less extensively to avoid overtreatment and reduce parents’ anxiety and medical care costs ( 30 32 ). It is known from other data that screening TSH tends to be lower in neonates with TCH than in those with PCH ( 17 , 33 35 ). In our study, decreased screening TSH results were observed in newborns with birth weight below -2 SDS who are mostly burdened with TCH risk.…”
Section: Discussionmentioning
confidence: 93%
“…The diagnosis of CH is confirmed by the thyroid function tests (TFTs) and thyroglobulin (TG) analysis and subsequent immediate treatment implementation with oral, solid or liquid, levothyroxine (L-T4). In PCH the treatment will be life-long, but up to 35% of newborns diagnosed with CH reveal to have TCH, which allows for a trial of L-T4 dose reduction or withdrawal after the critical period of neurodevelopment ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…This variability can be explained by many factors, such as the inclusion/exclusion criteria, the cutoff of TSH at DBS for diagnosis or the recall strategy, the age of discontinuation of therapy. If the condition of CH due to ectopic gland or athyreosis is also considered, this rate is reduced to 6.7–60% [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. In our current study, the TCH rate was 47.3% when considering only subjects with eutopic thyroid, and 24.8% when considering the whole cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have analyzed the risk factors for developing PCH by finding female gender, higher TSH and lower fT4 levels at diagnosis and higher levothyroxine requirement as predictors [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Our data confirm that the thyroid hormonal profile at diagnosis and the levothyroxine requirement upon discontinuation of treatment are predictive for the permanent condition, as well as the presence of extra-thyroid malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation